(untitled) (BIRDEM Medical Journal, 2018)
Background: Carpal tunnel syndrome (CTS) is one of the most frequent entrapment neuropathies of the upper limb. CTS and diabetic polyneuropathy (DPN) are common conditions in patients with diabetes and therefore frequently occur concomitantly. Diagnosis of CTS in patients with DPN is important, as therapeutic interventions directed toward relief of CTS may be effective irrespective of diffuse neuropathy. Methods: This study was a hospital based descriptive cross sectional study done in a tertiary care hospital, Dhaka between July, 2015 and June, 2016. The initial clinical diagnosis of diabetic peripheral neuropathy was made from history and examination. It was confirmed by doing nerve conduction study. After having informed written consents, a standard preformed questionnaire was filled up for each case. Collected data were checked, verified for consistency and edited for final results. Data cleaning, validation and analysis were performed using Statistical Package for the Social Sciences (Version 20.0). Results: A total of 354 cases were finally analyzed with 153 (43.2) patients being symptomatic for CTS and among those 54 (58.7%) had electrophysiology proven CTS. It was observed that 26.0% of patients established as having DPN also had CTS. The frequency of CTS among those with symptoms was significantly higher than in asymptomatic participants. The mean age was found to be 55.99 ± 9.25 years with a range from 28 to 80 years. Majority (38.4%) of patients belonged to the age group of 51-60 years. Among all cases of electrophysiology proven CTS (92 patients), females (53.3%) numbered greater in comparison to males (46.7%). One hundred and ninety two (54.2%) patients were housewives, 57 (16.1%) were garment workers, 45 (12.7%) patients were businessmen and 60 (16.9%) patients were service holders. Study subjects with CTS had significantly higher body mass index, higher fasting blood glucose and higher HemoglobinA1c in comparison to patients without CTS. Examination of upper limb sensory nerves showed that nerve conduction velocity was significantly decreased and distal latency was found to be significantly increased in patients with CTS on median nerve examination. The mean compound motor action potential was not significantly different between patients with and without CTS. Conclusion: Symptoms and signs of CTS are mostly masked by the symptoms of DPN and patients presenting with such symptoms in the upper limbs should be evaluated for CTS as a separate entity to DPN. The finding of a frequency of CTS of 26% in subjects with diabetes with varying degrees of DPN is remarkably high. Given the high prevalence of CTS in subjects with DPN, it is recommended that therapeutic decisions be made carefully after nerve conduction study and proper diagnosis. Birdem Med J 2018; 8(3): 246-250